2020
DOI: 10.3390/genes12010009
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 34a–AXL Axis Regulates Vasculogenic Mimicry Formation in Breast Cancer Cells

Abstract: Targeting the tumor vasculature is an attractive strategy for cancer treatment. However, the tumor vasculature is heterogeneous, and the mechanisms involved in the neovascularization of tumors are highly complex. Vasculogenic mimicry (VM) refers to the formation of vessel-like structures by tumor cells, which can contribute to tumor neovascularization, and is closely related to metastasis and a poor prognosis. Here, we report a novel function of AXL receptor tyrosine kinase (AXL) in the regulation of VM format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Metastasis remains as one of the more devastating cancer hallmarks, which account for most of cancer-related deaths. Notably, VM has been established a s a novel marker of poor prognosis in breast cancer patients, as it promotes resistance to therapy [ [20] , [21] ], and tumor progression [22] . Although the molecular mechanisms for VM development have been the objective of intense research, little is known about its regulation by ncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis remains as one of the more devastating cancer hallmarks, which account for most of cancer-related deaths. Notably, VM has been established a s a novel marker of poor prognosis in breast cancer patients, as it promotes resistance to therapy [ [20] , [21] ], and tumor progression [22] . Although the molecular mechanisms for VM development have been the objective of intense research, little is known about its regulation by ncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…We found two miRNAs, miR-34 and miR-193b, to be involved in the regulation of angiogenesis in both pubertal and cancer processes. MiR-34 is a tumour suppressive miRNA which has been found to reduce vasculogenic mimicry in breast cancer by targeting AXL tyrosine kinase [63]. Overexpression of miR-34a was also found to reduce invasion and migration.…”
Section: Angiogenesismentioning
confidence: 99%
“…The signaling of AXL receptor tyrosine kinase promotes cancer stem cell-like phenotypes, drug resistance, metastasis, and EMT. Overexpression of this receptor promotes the regulation of VM formation in breast cancer cells [ 73 ] through miRNA-34a that targets the 3’-untranslated region (UTR) [ 85 , 86 ]. In this sense, it was demonstrated that miRNA-34a overexpression downregulated AXL receptor expression resulting in the inhibition of VM formation, migration, and invasion in MDA-MB 231 cells [ 28 ].…”
Section: Vm Regulation By Noncoding Rnas In Breast Cancermentioning
confidence: 99%